Method of automatic steering system design and parameter optimisation for small tractors - Guangzhao Tian (The Journal of Engineering, 2019)
In order to improve the operational efficiency and quality of small tractors, the original manual steering system needs to be renovated to include automatic steering functionality, which is the basis of autonomous navigation. Here, a modification method based on the steering circuit of a Dongfanghong SG250 tractor and a method to calculate the virtual steering angle is proposed. A small tractor steering model is established from the step response data of the system, and a PD controller for this model is also designed. The PD controller can also adapt to varying tractor speeds for optimal functionality in changing operational conditions, and a parameter optimisation approach for the speed-adaptive PD controller is proposed. Test results show that at a speed of 0.5 m s^−1, the steady-state error in the step response is 0.32°, the percentage error is 2.3%, the overshoot is 1.86°, and the percentage overshoot is 13.7%. For a ramp response, the average signal latency is 0.82 s and the steady-state error is 0.25°. The ability of the PD to adapt to changing speeds is also tested at different speeds. The results show that the steering system performs well.